Factors influencing the intention of recipient to pay back education loan in state foundation - Nurul Farhanah, Mohd Idres; Hasnah, Haron; Mohd Hanafiah, Ahmad (KnE Social Sciences, 2019)
This paper explores the factors that influence the intention to pay back the education loan among students in a state foundation. Education loan is the primary source for the student in order to pursue their studies. The government has introduced many forms of financial assistance such as scholarship, grants and education loan. However, the loan recipients have faced difficulties in repaying the loan, which will affect the provider and future recipients. This is because, the loan provider will not be able to sponsor future students if they are not able to collect the loan from the loan recipients. This paper identifies attitude, parental influence, media awareness and perception of loan agreement towards the intention to pay back the education loan. Theory of Planned Behavior (TPB) is suggested to be the underpinning theory of this study. Findings of the study can assist the state foundations on setting strategies to collect payment from the loan recipients.